Effect of Pre-Planting Cold Treatment on the Growth and Development of Onion Seed Crop with Special Emphasis on Flowering - Islam, KS; Rahim, MA; Rehana, S (Progressive Agriculture, 2013)
This study was stimulated by the problem of onion seed production in Bangladesh and similar regions where seed production is possible only during the short cool winter period after which rapid increase in temperature as well as early shower adversely affect the quality of seed. Experiment was carried out inorder to develop suitable production techniques to get high yield and quality of onion seed overcoming the stated adverse situation. The present research was conducted at the Horticulture Farm, Department of Horticulture, BangladeshAgricultural University, Mymensingh and in the Plant Genetic Laboratory of Bangladesh Institute of Nuclear Agriculture (BINA), Mymensingh during the period from 1999 to 2000 to manipulate the control of growth cycle of onion for high yield and production of quality seed. The results revealed that the number of days required for 80% emergence of bulb, plant height, number of leaves per hill, days required to bolting, number of flower per umbel, number of seed set per umbel were significantly influenced by the temperature treatment. Results showed that seed crop development was accelerated by pre-planting cold treatments. Pre-planting cold treated seed crop enhanced bulb emergence and completed vegetative growth earlier, also early initiation of flower stalks, flowering, fruit setting, maturity and consequently quality seed. From preplanting cold treatment, seed crop was harvested at least 11-14 days before the non-treated ones. DOI: http://dx.doi.org/10.3329/pa.v21i1-2.16748 Progress. Agric. 21(1 & 2): 47 - 55, 2010